Relationship of Angle’s Molar Malocclusion with Facial Profile among School Children with the Age Group of 11 to 16 Years at Dhaka City in Bangladesh - Rahaman Tipu, Md Mizanur; Ghosh, Ranjit; Mafruha, Mst Ishrat; Chakraborty, Monika; Sharma, Nirmal (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Orthodontic care globally urges the need to develop various methods to assess and grade malocclusion in order to prioritize treatment Objective: The purpose of the present study was to describe Angle’s molar relationship among the study subjects with the facial profile. Methodology: This study was designed as a Descriptive Cross-Sectional study carried out in four high schools in Dhaka city, Bangladesh. The study was conducted from May 2015 to November 2015 for a period of 06 (six) months on 384 secondary school children aged between 11 – 16 years Systematic Random Sampling from four high schools in Dhaka city. The participants were included who had no preventive and interceptive orthodontic treatment previously carried out and participants having late mixed or early permanent dentition. The participants were excluded participants having major local problems such as trauma or any history of surgical approach which affects the growth and development of facial structures or body, Students who are undergoing orthodontic treatment or who have completed orthodontic treatment earlier, Students who are suffering from any systemic disease. Data were collected using a preformed data collection sheet. The relevant socio-demographic data of these patients were collected and recorded. Data were collected and Parents/ guardians were provided with a description of the study, an informed consent form (written in Bengali) and a family history/ lifestyle questionnaire (written in English). In addition, trained research assistants were explained the study procedures. Results: Out of 384 children, the maximum no. of Angle’s molar relationship was Class I in both sides, similarly maximum no. of Canine relationships was Class I in both sides. Maximum face form was oval (51.8%), maximum (57.6%) face profile was straight and maximum (76.6%) lips were competent. Conclusion: In this study, malocclusion was 56.7%. Angle’s class I malocclusion is the most common while Angle’s class III is the least prevalent malocclusion. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):206-209